Harnessing localised multi-actor institutional water, energy and food nexus financing to achieve just transitions in South Africa - Thulani Ningi; Saul Ngarava; Alois A. Mugadza (Sustainable Futures, 2025)
Achieving just transitions in South Africa requires integrated and inclusive financing across the water, energy and food (WEF) nexus. This study sought to examine how multi-actor institutional financing structures influence equity and coordination within the WEF nexus. Using a Social Network Analysis approach, data were collected from key informants representing public, private, and multilateral financial institutions involved in WEF-related projects. Network mapping and centrality metrics were applied to assess institutional interactions and coordination, using University of California Irvine NETwork (UCINET) version 6 for the analysis. The analysis revealed a sparse financing network, with a low-density score (0.062) and limited collaboration across decision-making levels. Key intermediaries, such as the Public Investment Corporation and the Land Bank, were identified as central actors, while local-level financing remained largely absent. The findings highlight the need to strengthen institutional synergies, foster cross-sectoral partnerships, and develop regional financing hubs to address fragmentation and promote inclusive sustainability transitions. The study provides targeted insights for policymakers and financial stakeholders working to realign funding systems with local development priorities and to accelerate equitable sustainability transitions.